2021
DOI: 10.1097/j.pain.0000000000002517
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of working memory and contralateral delay activity by nociceptive stimuli is modulated by task demands

Abstract: Top-down processes allow the selection and prioritization of information by limiting attentional capture by distractors, and these mechanisms depend on task demands such as working memory (WM) load. However, bottom-up processes give salient stimuli a stronger neuronal representation and provoke attentional capture. The aim of this study was to examine the effect of salient nociceptive stimuli on WM while manipulating task demands. Twenty-one healthy participants performed a change detection task during which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Third, it is possible that the design is not optimal to disclose difference in the power of steady-state evoked potentials. We only had a 2-min recording of steady-state evoked potentials during painful stimulation, in contrast with classical studies using several repetitions of the stimuli (Wagenaar-Tison et al, 2021). Moreover, to the best of our knowledge, all other studies combining EEG and nociceptive stimulation used a number of discrete nociceptive stimuli (e.g.…”
Section: Lack Of Difference In Cortical Responses To Repeated Electri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it is possible that the design is not optimal to disclose difference in the power of steady-state evoked potentials. We only had a 2-min recording of steady-state evoked potentials during painful stimulation, in contrast with classical studies using several repetitions of the stimuli (Wagenaar-Tison et al, 2021). Moreover, to the best of our knowledge, all other studies combining EEG and nociceptive stimulation used a number of discrete nociceptive stimuli (e.g.…”
Section: Lack Of Difference In Cortical Responses To Repeated Electri...mentioning
confidence: 99%
“…Research has shown that performing a cognitive task during acute nociceptive stimulation attenuates pain perception (Petrovic et al, 2000; Romero et al, 2013; Valet et al, 2004; Verhoeven et al, 2011). Indeed, cognitive load (Bantick et al, 2002; Deldar et al, 2021; Legrain et al, 2005; Moore et al, 2017; Seminowicz et al, 2007; Veldhuijzen et al, 2006; Wagenaar‐Tison et al, 2021; Wiech et al, 2005) and working memory (Buhle & Wager, 2010; Deldar et al, 2018, 2019; Do et al, 2020; Legrain et al, 2013; Legrain, Crombez, & Mouraux, 2011; Legrain, Crombez, Verhoeven, et al, 2011) may contribute to pain reduction, by shielding attention from the nociceptive input. This would be in line with limited‐capacity theories of attention (Broadbent, 1958; Kahneman, 1975; Lavie et al, 2004; Norman & Bobrow, 1975): The more attentional resources performing a cognitive task requires; the less resources remain available to process concomitant nociceptive stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Third, it is possible that the design is not optimal to disclose difference in the power of steady-state evoked potentials. We only had a 2-minute recording of steady-state evoked potentials during painful stimulation, in contrast with classical studies using several repetitions of the stimuli (Wagenaar-Tison et al, 2021). Moreover, to the best of our knowledge, all other studies combining EEG and nociceptive stimulation used a number of discrete nociceptive stimuli (e.g.…”
Section: Lack Of Difference In Cortical Responses To Repeated Electri...mentioning
confidence: 99%
“…Research has shown that performing a cognitive task during acute nociceptive stimulation attenuates pain perception (Petrovic et al, 2000;Romero et al, 2013;Valet et al, 2004;Verhoeven et al, 2011). Indeed, cognitive load (Bantick et al, 2002;Deldar et al, 2021;Legrain et al, 2005;Moore et al, 2017;Seminowicz et al, 2007;Veldhuijzen et al, 2006;Wagenaar-Tison et al, 2021;Wiech et al, 2005) and working memory (Buhle & Wager, 2010;Deldar et al, 2018;2019;Do et al, 2020;Legrain et al, 2011a;2011b; may contribute to pain reduction, by shielding attention from the nociceptive input. This would be in line with limited-capacity theories of attention (Broadbent, 1958;Kahneman, 1975;Lavie et al, 2004;Norman & Bobrow, 1975): The more attentional resources performing a cognitive task requires, the less resources remain available to process concomitant nociceptive stimuli.…”
Section: Introductionmentioning
confidence: 99%